2018
DOI: 10.20944/preprints201805.0211.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualization of Annular Gap Junction Vesicle Processing: The Interplay between Annular Gap Junctions and Mitochondria

Abstract: It is becoming clear that in addition to gap junctions, playing a role in cell-cell communication, gap junction proteins, connexins, located in cytoplasmic-compartments may have other important functions. Mitochondrial connexin 43 (Cx43) is increased after ischemic preconditioning and has been suggested to play a protective role in the heart. How Cx43 traffics to the mitochondria and the interactions of mitochondria with other Cx43-containing structures are unknown. In this study, immunocytochemical, super-res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…GJA1 is extremely important for maintaining mitochondrial integrity (Kim, Kwon, Im, et al, ). In the blockade of GJA1 to mitochondrial membrane transfer, myocardial hypoxia injury induced by cobalt chloride (CoCl 2 ) can be aggravated (Pecoraro, Pinto, & Popolo, ), whereas in myocardial cells pretreated with ischemia‐reperfusion injury, the expression of mitochondrial GJA1 is significantly increased (Bell, Shakespeare, Smith, et al, ). Our previous studies also showed that GJA5, which is compensated for GJA1 phosphorylation after brain injury, is closely related to the activation of oxidative stress associated with mitochondrial‐endoplasmic reticulum dysfunction (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…GJA1 is extremely important for maintaining mitochondrial integrity (Kim, Kwon, Im, et al, ). In the blockade of GJA1 to mitochondrial membrane transfer, myocardial hypoxia injury induced by cobalt chloride (CoCl 2 ) can be aggravated (Pecoraro, Pinto, & Popolo, ), whereas in myocardial cells pretreated with ischemia‐reperfusion injury, the expression of mitochondrial GJA1 is significantly increased (Bell, Shakespeare, Smith, et al, ). Our previous studies also showed that GJA5, which is compensated for GJA1 phosphorylation after brain injury, is closely related to the activation of oxidative stress associated with mitochondrial‐endoplasmic reticulum dysfunction (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Direct imaging of living cultured cells has shown that connexosomes are formed by internalization of entire gap junctions, and that connexosomes can undergo fission (Piehl et al, 2007;Bell et al, 2018). We examined the high pressure frozen and serial sectioned ovarian follicles for connexosome formation.…”
Section: Connexosome Formationmentioning
confidence: 99%
“…The surface areas of invaginated gap junctions are significantly larger than connexosomes based on one-way ANOVA analysis. In live imaging of Cx43-GFP expressing cells, connexosomes were observed to undergo fission (Piehl et al, 2007;Bell et al, 2018). In ovarian follicle cells, the connexosomes may also undergo fission after internalization; alternatively, they could form from a portion of a larger invaginated gap junction.…”
Section: Connexosome Formationmentioning
confidence: 99%
“…Direct imaging of living cultured cells has shown that connexosomes are formed by internalization of entire gap junctions, and that connexosomes can undergo fission (Piehl et al, 2007;Bell et al, 2018). We examined the high pressure frozen and serial sectioned ovarian follicles for connexosome formation.…”
Section: Connexosome Formationmentioning
confidence: 99%
“…Live cell imaging studies of several cultured mammalian cell lines expressing Cx43-GFP chimeras showed that either entire gap junctions are internalized, followed by fission (Piehl et al, 2007;Bell et al, 2018), or that a small portion of the gap junction center is internalized (Falk et al, 2009).…”
Section: Connexosome Formationmentioning
confidence: 99%